XAIPE MAPIA annunciation imagery in the making - Lidova, M (Brepols Publishers, 2017)
The paper provides an overview of the earliest surviving images of the Annunciation. It demonstrates that the iconography of this scene went through a number of formative stages in early Christian period and this transformation is indicative of the changing perception of the event and the development of the theological tradition in relation to the theme of incarnation. In the 3rd and 4th centuries, images of the Annunciation are exceptionally rare, and the rendering of the scene is dependent on the Roman visual tradition. From about 400, the representation of the basket with loom and the purple thread held by Mary become indispensable elements of the Annunciation imagery, a shift reflected in the monuments coming from both Eastern and Western parts of the Empire. This change reveals not only the growing cult of Mary, but also the great role played by the apocryphal sources in the creation of the visual ”texture” of narrative compositions connected to the Virgin. Furthermore, it coincides with and echoes the contemporary homiletic tradition, which attributed deep religious meaning to the process of weaving, and the making of the garments, and of the temple veil, all associated with Christ’s body and the mystery of incarnation. Finally, it is demonstrated in the paper that the apocryphal Annunciation at the Spring was equally popular at the time and regularly substituted for images of the Annunciation in the House in the narrative cycles focused on the figure of Mary.